2017
DOI: 10.1097/mib.0000000000001093
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Clinical Outcomes in an IBD Cohort Who Have Previously Had Anti-TNFa Trough and Antibody Levels Assessed

Abstract: LOR is still a big concern with anti-TNFa therapies. Stand-alone anti-TNFa trough and antibody levels are not useful at predicting LOR/disease progression at 1 year, but low trough levels do correlate well with elevated CRP, hypoalbuminaemia, and poor response rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…There is however a lack of association between once off maintenance phase immunomonitoring with outcomes. Our group have done a retrospective analysis of 82 patients on maintenance infliximab and adalimumab, and we found no association between once off, anti-TNFα trough and ADA levels, with clinical response, similar to other data[ 72 ]. In future, event triggered immunomonitoring may be the best approach to incorporate immunomonotoring.…”
Section: Application Of Immunomonitoringsupporting
confidence: 88%
“…There is however a lack of association between once off maintenance phase immunomonitoring with outcomes. Our group have done a retrospective analysis of 82 patients on maintenance infliximab and adalimumab, and we found no association between once off, anti-TNFα trough and ADA levels, with clinical response, similar to other data[ 72 ]. In future, event triggered immunomonitoring may be the best approach to incorporate immunomonotoring.…”
Section: Application Of Immunomonitoringsupporting
confidence: 88%
“…A primary failure to respond to anti‐TNF treatment affects 13–40% of patients with CD and secondary response loss occurs in 23–46% of patients. In other studies, 10–30% of patients with IBD showed no initial clinical benefits after anti‐TNF therapy and more than 50% that had an initial favorable outcome lost the effect over time . In addition, a high proportion of patients with IBD relapse after anti‐TNF treatment is stopped .…”
Section: Introductionmentioning
confidence: 95%
“…In other studies, 10-30% of patients with IBD showed no initial clinical benefits after anti-TNF therapy and more than 50% that had an initial favorable outcome lost the effect over time. 15,16 In addition, a high proportion of patients with IBD relapse after anti-TNF treatment is stopped. 17,18 The overall risk of relapse after discontinuation was found to be 44% for CD and 38% for UC.…”
Section: Limitations Of Parenteral Administration Of Anti-tnf Agentsmentioning
confidence: 99%
“…This has led to introducing biologically based therapies (i.e., anti-TNFα) in IBD patients. However, achieving adequate response levels still remains elusive as stand-alone anti-TNFα therapies have not proven completely useful at predicting disease progression and drug response [ 54 ]. Recently, animal models suggested that the lack of response could be related to differences in the gut microbiome before and after disease initiation.…”
Section: Epigenetics and Ibdmentioning
confidence: 99%